Characterization of differences in substrate specificity among CYP1A1, CYP1A2 and CYP1B1: an integrated approach employing molecular docking and molecular dynamics simulations. Issue 8 (25th February 2016) - Kesharwani, Siddharth S.; Nandekar, Prajwal P.; Pragyan, Preeti; Rathod, Vijay; Sangamwar, Abhay T.
Abstract : Recent trends in new drug discovery of anticancer drugs have made oncologists more aware of the fact that the new drug discovery must target the developing mechanism of tumorigenesis to improve the therapeutic efficacy of antineoplastic drugs. The drugs designed are expected to have high affinity towards the novel targets selectively. Current research highlights overexpression of CYP450s, particularly cytochrome P450 1A1 (CYP1A1), in tumour cells, representing a novel target for anticancer therapy. However, the CYP1 family is identified as posing significant problems in selectivity of anticancer molecules towards CYP1A1. Three members have been identified in the human CYP1 family: CYP1A1, CYP1A2 and CYP1B1. Although sequences of the three isoform have high sequence identity, they have distinct substrate specificities. The understanding of macromolecular features that govern substrate specificity is required to understand the interplay between the protein function and dynamics, design novel antitumour compounds that could be specifically metabolized by only CYP1A1 to mediate their antitumour activity and elucidate the reasons for differences in substrate specificity profile among the three proteins. In the present study, we employed a combination of computational methodologies: molecular docking and molecular dynamics simulations. We utilized eight substrates for elucidating the difference in substrate specificity of the three isoforms. Lastly, we conclude that the substrate specificity of a particular substrate depends upon the type of the active site residues, the dynamic motions in the protein structure upon ligand binding and the physico‐chemical characteristics of a particular ligand. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Understanding the substrate specificity within CYP1A1, CYP1A2 and CYP1B1 may reduce the attrition of anticancer drugs, target to CYP1A1, in drug discovery and development. Herein, we employed recent computational methodologies including molecular docking and molecular dynamics simulations to explore the key points responsible for substrate specificity in the CYP1 family. The active site residues, the dynamic state of the proteins in binding with the substrates and physicochemical properties of substrates contribute to the substrate specificity in the CYP1 family.